"HAMKA-CCOUNTING": DEFINING THE PHILOSOPHY OF HAMKA'S POLITICAL ECONOMY OF ACCOUNTING - Resi Ariyasa Qadri (Bina Ekonomi, 2024)
This research introduces "Hamka's Political Economics of Accounting," reconceptualizing the Political Economy of Accounting (PEA) through Hamka's political and economic philosophies. Hamka's perspectives were profoundly integrated with his Islamic convictions, promoting social justice, economic parity, and political frameworks that adhere to Islamic principles. By utilizing literature documentation for data collection and a Kuhnian deconstruction process for analysis, the study identifies three core traits in Hamka's revision of PEA: the imperative of addressing social conflicts and power dynamics in accounting, the importance of contextualizing accounting within specific cultural and organizational settings, and advocating for a more liberated perspective on the societal role of accounting. Hamka posits a universal principle that transcends national and cultural boundaries, advocating for a shared pursuit of justice and truth. This principle serves as a cornerstone, linking the political economy with societal issues and offering a novel lens for understanding the interplay between accounting practices and socio-political dynamics. This study contributes to the discourse on the political economy of accounting by providing a unique theoretical framework that integrates accounting practices within their broader socio-political contexts.